RESTORATIVE JUSTICE IN RESOLVING EMBEDDING AT CIREBON CITY POLRES - Monica Octavia; Sanusi; Alip Rahman (International Peneliti Ekonomi, Sosial dan Teknologi, 2021)
The settlement of the crime of embezzlement by using restorative justice provides the best solution in resolving private crime cases between people (natuurlijkepersonen) or legal entities (recht personen). The implementation of restorative justice in the settlement of criminal acts of embezzlement at the Cirebon City Police has been carried out, but there are obstacles. The research uses an empirical juridical approach, by means of field research, namely examining legal regulations which are then linked to data and behavior that lives in the midst of society in the form of primary data. Research shows that restorative justice is the process of resolving criminal cases by involving victims of crime, criminals and representatives in society to be able to meet together to find common ground that will benefit both parties. The concept of applying restorative justice in cases of criminal acts of embezzlement is better than the criminal system and the conventional judicial process which takes a long time and costs a lot from both the victim and the government itself in terms of facilitating the examination process, up to the execution process of the embezzlement case. alone. Restorative justice is a fast, simple and low-cost means of settlement which allows it to be used in the settlement of criminal cases of embezzlement as an offense with a private dimension between the victim and the perpetrator of the crime. The obstacle is that people don't know much about restorative justice, especially the model so that many people don't want to be solved with restorative justice. The application of restorative justice should be applied to every criminal case if the perpetrator and the victim want it, not just a case of embezzlement.